Distribution of Rhodophyta in streams from São Paulo State, southeastern Brazil - Necchi, O.; Branco, CCZ; Branco, LHZ (E Schweizerbart'sche Verlags, 1999)
Distribution of Rhodophyta was investigated in 172 stream segments, which were sampled from May to October in 1992-1993 and 1996-1997 in six natural regions (parts of biomes or geological areas) of São Paulo State, southeastern Brazil. Red algae occurred in 60.5 % of stream segments sampled, a high frequency in comparison with other major surveys in the world (18-65 %). 17 species of freshwater red algae were found, of which the most widespread was Batrachospermum delicatulum occurring in 17 sites of five regions. The proportion of morphological types was as follows: gelatinous filaments (62.5 %), free filaments (19 %), tufts (12.5 %) and crusts (6 %); all but free filaments can be considered as having mechanisms to tolerate stress provoked by current velocity. No significant difference was found between the frequency distributions of variables measured for all streams and for those with red algae. Rhodophyta occurred under the following conditions (means): temperature (19.0 degrees C), current velocity (48 cm s(-1)), specific conductance (74 mu S cm(-1)), turbidity (8 NTU), oxygen (67.3 %) and pH (6.9 +/- 0.7). on the basis of species composition among the regions, the following patterns were evident: 1) the number of red algal species per region ranged from 1 to 10; 2) the highest proportion of sites with red algae (65-73 %) was found in hard water regions and in Atlantic rainforest, whereas the lowest (50 %) was found in tropical rainforest; 3) more than half of the species were exclusive from a single region, whereas the higher proportion of exclusive species was in the subtropical rainforest (50 %). No combination of stream variables was clearly associated with the occurrence of red algae for the regions as a whole. Species composition for streams and rivers of São Paulo State revealed higher similarities with other tropical regions and had few species in common with freshwater red algal floras of other continents.